2010
DOI: 10.1016/s1028-4559(10)60101-5
|View full text |Cite
|
Sign up to set email alerts
|

Ellis-Van Creveld Syndrome: Prenatal Diagnosis, Molecular Analysis and Genetic Counseling

Abstract: Prenatal sonographic identification of endocardial cushion defects in association with shortening of the long bones should alert clinicians to the possibility of EvC syndrome and prompt a careful search of hexadactyly of the hands. Molecular analysis of the EVC and EVC2 genes is helpful in genetic counseling in cases with prenatally detected postaxial polydactyly, thoracic narrowness, short limbs and endocardial cushion defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 39 publications
0
12
0
3
Order By: Relevance
“…2 The syndrome is rare with a prevalence of 0.7 per 100 000 live births. An increased frequency is registered among the Amish community in Lancaster county and some Arab population, with a prevalence of 5 per 1000 and 5.2 per 100 000 live births, 3 respectively. Genetic studies have demonstrated that EVC syndrome is because of mutations in the EVC and EVC2 genes.…”
mentioning
confidence: 99%
“…2 The syndrome is rare with a prevalence of 0.7 per 100 000 live births. An increased frequency is registered among the Amish community in Lancaster county and some Arab population, with a prevalence of 5 per 1000 and 5.2 per 100 000 live births, 3 respectively. Genetic studies have demonstrated that EVC syndrome is because of mutations in the EVC and EVC2 genes.…”
mentioning
confidence: 99%
“…To date, 77 mutations in the EVC gene and 67 mutations in the EVC2 gene have been published in the Human Gene Mutation Database at the Institute of Medical Genetics in Cardiff (http://www.hgmd.org); most of them are nonsense, splicing and frameshift mutations, with truncating protein as a final consequence. Anomalies of EvCS include a narrow thorax, marked shortening of the long bones, postaxial polydactyly of the hands and feet, and cardiac defects frequently seen prenatally . Here, we report the prenatal findings and genetic analysis of a terminated pregnancy affected by severe thoracic and skeletal dysplasia, which then was revealed to be EvCS.…”
Section: Introductionmentioning
confidence: 94%
“…As one of the rarest ciliopathies, its precise prevalence is unknown but is estimated to have a low prevalence of 7/1,000,000 in the general population. It has been reported as most prevalent in Amish, Brazilian, Ashkenazi Jewish, and Arab populations due to consanguinity (Al‐Fardan & Al‐Qattan, ; Chen et al, ; Shaik et al, ). EVC patients may have abnormal skeletal and extraskeletal manifestations, including disproportionate short‐limb dwarfism, narrow chest, cubitus valgus, genu valgus, postaxial polydactyly, sparse hair, multiple oral frenula, nail and teeth dysplasia, and congenital heart defects (Chen et al, ; Fischer et al, ; Ibarra‐Ramirez et al, ; Rao, Sahu, Kareem, Devasia, & Shetty, ; Valencia et al, ).…”
Section: Introductionmentioning
confidence: 99%